Jezuickie kolegia szlacheckie w Europie Zachodniej. Rekonesans - Puchowski, Kazimierz (Horyzonty Wychowania, 2017)
This article presents the establishment and development ofJesuit colleges for nobility in Western Europe. The activity of theseschools expressed consideration for the elite’s educationalaspirations in the order policy. Private boarding schools, servinga selected group of young people, in terms of ideology, organizationas well as programme, constituted a certain anomaly inJesuit educational system. They were also an expression of theselective approach to egalitarianism propagated in KonstytucjeTowarzystwa Jezusowego (The Constitutions of the Society ofJesus) and Ratio studiorum (1599). Responding to the educationalaspirations of the upper classes, Jesuits were reformingsecondary school. Selective implementation of elements of theprogramme and methods adopted in knight’s academies did notshake the foundations of humanistic tradition, but the aim of theinstitutions for nobility was essentially different from the oneascribed to knight’s academies. Jesuits wanted to shape theirstudents devoted to Church and at the same time strengthen theorder’s influence among clerical and lay elite. The initiative regardingestablishment of schools for elite involved mainly kings,whose aspiration was that exclusive schools educate competentpeople devoted to monarchy. School founders – monarchs andprinces presented their own aspirations and demands to theorder, thus individual colleges had their own flavour in terms oforganization and programme. The author of the article indicatesthat despite popular opinion in Polish historiography, Jesuits, andnot Piarists were the first to modify secondary schools andestablish collegia nobilium. Jesuits understood that running suchinstitutions for aristocrats’ sons (in France also for the sons ofwealthy burgesses) offers an opportunity to take over a certainstrategic function, that is control over education of those whowould assume power in the centralizing state.